The bully book - Gale, Eric Kahn, 1986- (New York : Harper, 2013)
Eric Haskins feels like everyone is picking on him, but when he discovers a conspiracy theory about a bully book that reveals a framework for gaining power in the school by turning everyone against one kid known as a grunt, Eric finds himself on the trail of huge secrets at Arborland Elementary School.
Publisher's Weekly, November 2012
Kirkus Review, November 2012
Includes bibliographical references.
3.9
3-6
HL620L
Keywords: Bullying -- Juvenile fiction; Schools -- Juvenile fiction; Secrecy -- Juvenile fiction; Bullies -- Fiction; Schools -- Fiction; Secrets -- Fiction